Profit, productivity and price performance changes in the English and welsh water and sewerage companies - Alexandros Maziotis; David S. Saal; Emmanuel Thanassoulis (Fondazione Eni Enrico Mattei (FEEM), 2012)
The purpose of this paper is to assess the impact of regulation in the financial performance of the Water and Sewerage companies (WaSCs) in England and Wales. We apply a panel index approach across WaSCs over time to decompose unit-specific (temporal) index number based profitability growth as a function of the profitability, productivity and price performance growth achieved by benchmark firms, and the catch-up to the benchmark firm achieved by less productive firms. The results indicated that the steady decline in average price performance, gains in productivity and relatively stable economic profitability after 2000, suggest that Ofwat is now more focused on passing productivity benefits to consumers, and maintaining stable profitability than it was in earlier regulatory periods. This technique is of great interest for regulators to evaluate the effectiveness of regulation and companies to identify the determinants of profit change and improve future performance, even if sample sizes are limited.
Keywords: Q5; 330; Profit Decomposition; Productivity; Price Performance; Panel Index Numbers; Regulation; Water and Sewerage Industry; Wasserwirtschaft; Abwasserwirtschaft; Regulierung; Rentabilität; Produktivität; Dekompositionsverfahren; England; Wales